Analisis Kontrastif Daripada Aspek Fonologi Antara Bahasa Jepun Dan Bahasa Mandarin Dalam Sebutan Nombor = Contrastive Analysis Of Phonological Aspect In Number Articulation In Japanese And Mandarin Language - Kang, Mei Feng; Syahrina, Ahmad; Jamal Rizal, Razali (Global Business and Social Entrepreneurship Resources, 2017)
In this paper, the researchers will conduct a comparative analysis between Japanese and Mandarin language in terms of phonology. Both languages have a long history and relationship that can be traced back to the Han Dynasty (206 BC - 220). More specific, the analysis will be focusing on the similarities and differences between both languages in the process of numbers articulations. This context can be summarized under the phonology study which involving study, analyze, description and also the discussion about the sequence of language sounds (Fromkin & Rodman 1998: 96). In this study, data were obtained from recordings of the native speakers of Chinese students whom enrolled in Japanese language courses at Universiti Malaysia Pahang. Data is recorded in a controlled situation to ensure it captured clear and accurate sound for analysis. From the analysis, there are similarities and differences between the sound exists in both languages in the process of articulation of numbers. For example, an articulations of number 1 (one) in Mandarin is "一(yī)", while in Japanese is "一/ いち(ichi)". Both languages produce vocal sound "i" are the same but have different consonant sounds of "y" and “ch". From the perspective of second language acquisition and foreign language teaching, articulation skills or income noises pronunciation (articulation) is one of the important and necessary skills to master by the students. This is also indicate that the pronunciation differences will produce different meanings. If this situation occurs, the basic conditions for the communication process which is sharing the meaning of words will not occur.